Adenoma viloso com transformação carcinomatosa da ampola de Vater - Bravo Neto,Guilherme Pinto (2001)
Villous adenomas of the duodenum and ampulla of Vater are uncommon, but they have been diagnosed more frequently with the increasing use of upper gastrointestinal endoscopy. Differential diagnosis with villous adenocarcinoma may be difficult. The authors present a case of a 47-year-old man with a giant villous adenoma of the duodenum, with intermittent jaundice, that was treated by pancreatoduodenectomy.